Influences of the effective use of a computer simulation on learning in physical science - Adil Hamamous; Nadia Benjelloun (International Journal of Evaluation and Research in Education (IJERE), 2023)
One of the most attractive instruments in science education is digital simulation. The investigations were conducted utilizing a pre-test and post-test methodology with Moroccan students enrolled in the second year of the natural sciences option secondary certificate at the Abdellah Laroui High School in the city of Fez. In this paper, we assess the effects of including a digital simulation on high school students’ understanding of RLC (a linear circuit containing an electrical resistance, an inductor, and a capacitor) (25 students). There is a substantial difference between the means of the tests administered to the control (M-Cont) and experimental (M-Exp) classes (M-Exp-M-Cont=15.32–3.08=2.24>0), based on a student’s analysis of the two classes’ test scores using a t-test. This study found that using a digital simulation in an educational setting allows for the acknowledgment of the added value and has a favorable impact on student learning, notably in the study of free oscillations in an RLC circuit.